Persepsi Masyarakat terhadap Partai Politik di Desa Terantang Kecamatan Mandastana Kabupaten Barito Kuala - Zainal Zainal (Jurnal Pendidikan Kewarganegaraan, 2015)
At therecentcrisisof confidenceinvariousfields of human lifecaused by thebehaviorof the political elitethatbad in the eyesof society, publicapathytowardselectionsbecausethey arefilled fromelections,the leader ofthe previous year. The electionsare changingfrom year to year, the more advancedamoremoderntimesitis alsothe development ofsocietyandthought. Poorpublicperceptionof politiciansdue toincreasinglyopensociety toaccesspoliticalinformation. Publictend to viewpoliticiansasthe pursuerspersonal gain. Like totalkpositivelyabouthimselfalone, withoutthought tofulfillthe promiseutteredduring the campaign, let alonefight forthe aspirations ofthe publicThe purposeof thisstudyis1.To find outhowthe publicperceptionof thepolitical party2.To find outwhat lies behindthe peopledo notusetheir right to voteinelections of regional headsanddeputyheads. The data sourceconsists ofprimary and secondary datasources, primarydata sourcesobtainedfromthe head ofthe villageandcommunityinterviewswhilesecondarydata sourcesobtainedfromthe villageprofile data.Data collection techniquesusedwere interviews, observationanddocumentation. The data analysis techniquethat is byreducing the data, and thendisplaythe dataand thefinalconclusions.The results ofthis study indicate(1) the public perception ofpolitical partiesinthe VillageDistrict ofMandastanaTerantangBarito KualathatvillagersTerantangin viewpolitical parties have anattitudethatPolitis, Apathy, andLogical. (2) The background ofthe peopledo notusetheir right to voteinelections of regional headsanddeputyheadsthatpeople will prefer toworkinstead of usingtheir right to vote, polling stationsthat were locatedfar enoughto make peopledo notvote in elections(technical factors), do notknowanddid notknowof thecandidateswho ran forpublicandrationalfactors.Suggestionsinthis study isexpected tosociety1.change the mindsetaboutthe importance ofvoting2.Theballotis expected to bereached bythe votersso thatis not areason forvoterstoabstain from votingat the polls(3) Insteadofthecommitteevotingsoundin the villageTerantangprepare the meansof transportationshuttlefree of charge forvoterswho live farfromthe polls.Keywords:Public Perception, Political Party